Currículos emancipatórios para a educação de jovens e adultos na perspectiva das políticas públicas: resistências e esperanças - Possani, Lourdes de Fátima Paschoaletto (2008)
This paperwork is about the construction of emancipatory curriculum for Young and Adult Education Students (EJA) in the public policy perspective. The starting point for the research to be carried out was the EJA's Curricular Reorientation experience, ocurred in São Paulo city, from 2001 to 2004, presented here starting from the narratives of the educational managers involved in the public policy's formation and execution at that moment in the city of São Paulo. The voices of these managers are charged whith hope, bearing a glance wich announce the municipal public system's possibilities and limits in the construction of a new curriculum for a city as big and as complex as a metropolis. EJA's curricular reorientation movement had, as premise, the existence of social exclusion, as well as school exclusion, and the belief that the Young and Adult Education Students, in the freirean education vision, had an important role in social transformation, specially if we consider the possibility of constructing curriculum which aim people's emancipation. It was possible to conclude that, in order to craft emancipatory curriculum for EJA, it is necessary to consider the uthopic, ethical and educational action fields, besides conciliating the political, governamental and pedagogical action times. Although the school is a privileged space for the curriculum elaboration, the curriculum cannot be disconnected from other educative spaces and social sectors, where the young and the adult live their quotidian experience, intimately linked to the world of work and culture